Contriving Human Capital Practices Which Influence Organizational Commitment: Reimagine Future Skills of HR - Patra, Yogita; Tripathi, Shruti (Prabandhan: Indian Journal of Management, 2019)
The workforce in the IT industry has been in a constant mode of change. The workforce has evolved to be digital, technology savvy, social media proficient, and the way decisions need to be made to manage the workforce in the organizations have changed drastically. Some HR professionals found the match between the two challenging. However, by prioritizing the arenas of human capital management where attention is required, myriad opportunities could be found which HR could leverage to create reciprocity for organizational commitment from the employees. This changed landscape requires fresh thinking. The HR department needs to step up its role to manage competitive threats by creating new strategies. The goal set out for this paper was to contrive human capital management practices and understand where the focus should lay. After three rounds of Delphi survey, experts suggested seven human capital practices that demanded attention. The findings of Delphi survey were strengthened using stepwise multiple regression analysis to predict organizational commitment. Considering the paradigm shift required in the thought process, the findings of this study provided implications for HR in redefining its critical skills required in the future, which have been discussed at the end. The present study contributed to establishing the relationship between model based evolved HR practices for the new age and organizational commitment using empirical methods. The study contributed to HR function by developing a framework using the findings of the empirical study model which would motivate HR functions to redefine the role of HR professionals with the new age skills required for the present times.